Hypothesis: Potassium sparing by angiotensin and aldosterone inhibitors preserves skeletal muscle mass in chronic heart failure - Lara Zwakman‐Hessels; Miriam Zeillemaker‐Hoekstra; Maarten W. Nijsten (Wiley, 2020)
Abstract Background Cachexia complicates many chronic diseases. In chronic or congestive heart failure (CHF), cachexia independently contributes to decreased survival. Although diuretics have long been part of standard treatment of CHF, the addition of angiotensin and aldosterone antagonists to the standard treatment regimen has considerably improved the outcome of CHF. Both loop diuretics and the up‐regulation of the renin-angiotensin-aldosterone system caused by CHF induce loss of total body potassium (TBK). Hypothesis In addition to the causal association of loss of muscle mass with loss of TBK, we propose that the reverse mechanism also exists. The known beneficial effects of angiotensin and aldosterone inhibition may partly result from preserved TBK with consequent muscle mass preservation. Conclusion We propose that monitoring of muscle mass, potassium balances, and TBK should be included in future CHF studies to verify this hypothesis and allow further optimization of therapy.